Early vs delayed insertion of penile prosthesis in patients with refractory priapism: a systematic review and meta-analysis - Mohamed Elmarasi (14614276) (2024)
Introduction Refractory priapism, characterized by persistent and prolonged painful erections despite initial treatment maneuvers, can significantly impair erectile function secondary to ischemia-induced corporal tissue fibrosis. These patients will likely require subsequent penile prosthesis (PP) surgery to regain sexual activity, yet consensus regarding the optimal timing of implantation remains lacking. Objectives To evaluate and compare the clinical outcomes associated with early vs delayed PP implantation in individuals with priapism-induced erectile dysfunction (ED). Methods We included studies that focused on refractory priapism leading to ED and its management with PP implantation. We assessed cohort study bias with a risk-of-bias tool and case series bias with the modified Newcastle-Ottawa Scale. Pooled odds ratios (ORs) were calculated by a fixed-effect model. Results We included 9 studies, comprising 4 cohort studies and 5 case series, involving a total of 278 patients. Total complications were higher in the delayed group (OR, 4.16; 95% CI, 2.77-6.26). Fibrosis was significantly more pronounced in the delayed group (OR, 118.18; 95% CI, 20.06-696.32). The odds of erosion, infections, and penile injury did not show statistically significant differences between the groups (OR, 2.52 [95% CI, 0.67-9.49], 0.89 [0.38-2.10], 1.83 [0.79-4.26], respectively). Patients’ satisfaction resulted in a pooled OR of 0.15 (95% CI, 0.04-0.49) in favor of the early PP insertion group. Conclusion The results from this study favor an early approach to ED (within 30 days) following ischemic priapism. However, it is important to consider patients’ preferences, values, and psychological factors to make an informed decision. Other Information Published in: Sexual Medicine Reviews License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/sxmrev/qeae007